Legal Liability of Notaries for Formal Defects in Deeds of Guarantee as Instruments of Evidence in the Resolution of Financing Disputes: An Analysis Based on the Theory of Evidence and the Theory of Legal Responsibility - Elsa Novitri; Budi Santoso; Elli Ruslina (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2026)
This study examines the legal liability of notaries for formal defects in security deeds and their implications for the evidentiary value of such deeds in the resolution of financing disputes. Authentic deeds serve as a primary legal instrument for ensuring certainty in high-risk financing transactions; therefore, any formal non-compliance may significantly affect their probative force. The central issue addressed in this research is how formal irregularities influence the evidentiary strength of security deeds and to what extent a notary may be held liable when such defects result in losses to the parties involved. This research employs a normative legal method, applying statutory, conceptual, and case-based approaches. The findings demonstrate that formal defects may undermine both the external and formal evidentiary validity of security deeds, potentially degrading their status to private deeds. Such a shift weakens the creditor’s evidentiary position and impairs the effective enforcement of secured rights. From the perspective of liability theory, notarial accountability is generally fault-based, requiring proof of negligence or intent, actual damage, and a causal nexus between the notary’s conduct and the loss incurred. The novelty of this article lies in the development of an integrated analytical framework that bridges evidentiary theory and liability theory to distinguish between reparable formal defects and fatal defects that directly diminish evidentiary force. The study underscores the necessity of strict procedural compliance, heightened professional diligence, and proportionate accountability mechanisms to safeguard legal certainty in financing practices while preserving the institutional independence of the notarial profession.